The prospects of developing catering services in Ukraine - Melkumova, D. (ТДАТУ, 2018)
Modern trends in restaurant business are largely intangible – this type of activity is rapidly developing and creates new unique features. Recently, the trend has begun to shift the services of organizing consumption of products and servicing consumers from catering halls to other places. One of the newest branches of restaurant industry is catering.
Keywords: catering; restaurant business; Ukraine; service